2011
DOI: 10.1016/j.watres.2010.09.027
|View full text |Cite
|
Sign up to set email alerts
|

Cork industry wastewater partition by ultra/nanofiltration: A biodegradation and valorisation study

Abstract: Abstract:Wastewater from cork processing industry present high levels of organic and phenolic compounds, such as tannins, with a low biodegradability and a significant toxicity. These compounds are not readily removed by conventional municipal wastewater treatment, which is largely based on primary sedimentation followed by biological treatment. The purpose of this work is to study the biodegradability of different cork wastewater fractions, obtained through membrane separation, in order to assess its potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 9 publications
2
20
0
1
Order By: Relevance
“…The operating conditions were set in a way that polarization concentration was minimized, i.e. the feed flowrate was set for the maximum value and the transmembrane pressure was kept as low as possible . Other characteristics of this type of membranes have been reported previously by the authors …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The operating conditions were set in a way that polarization concentration was minimized, i.e. the feed flowrate was set for the maximum value and the transmembrane pressure was kept as low as possible . Other characteristics of this type of membranes have been reported previously by the authors …”
Section: Methodsmentioning
confidence: 99%
“…These wastewaters were characterized by Minhalma et al . and it has been shown that values for pH (4.97–5.1), COD (2230–7262 mg O 2 L ‐1 ) and BOD 5 (1125–2642 mg O 2 L ‐1 ) are well outside the LEV (limit emission value according to EU directive 91/271/CEE, 6.0 < pH < 9.0; COD < 150 mg L ‐1 ; BOD 5 < 40 mg L ‐1 ) making its release to the environment, without appropriate treatment, hazardous . Total polyphenols and tannin content in these wastewaters can rise to 1.0 g L ‐1 and 0.7 g L ‐1 , respectively, after 4 days of the boiling process, and a low degree of biodegradability (BOD 5 /COD = 0.3) was also observed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…NF membrane had nominal molecular weight cut-off (MWCO) ranging from 90 to 1000 Da, which could be selected to make the high retention of compounds with molecular weight of over 300 Da molecules. Thus, NF technology had a wide range of applications in various aspects for peptides fractionation, sugar concentration and waste water recycling [13,15,16]. UF and NF membranes have been applied for removing cyanotoxins [17], fractionating whey-derived peptides [16], recovering polyphenols from bergamot juice [18], refining soluble products from rice husk xylan [19] and recycling dairy wastewater [20].…”
Section: Introductionmentioning
confidence: 99%
“…This presents high acute toxicity for several tested organisms [4,5], which means that CBW has to be treated before disposal. The studies undertaken regarding CBW treatment comprise simple and combined methodologies that have been largely based on physical and chemical processes, such as: ultrafiltration and/or nanofiltration [6-11]; flocculation/flotation/ultrafiltration [12]; ozone and membrane filtration [13]; ozonation combined with hydrogen peroxide and UV radiation [14,15]; solarphoto-Fenton and solarphotocatalysis [16,17]; and Fenton oxidation-coagulation/flocculation [18]. However, many of these treatments are expensive and may give rise to pollutants.…”
Section: Introductionmentioning
confidence: 99%